Recurrent papulonecrotic tuberculid in an adolescent male: A diagnostic dilemma - Arundhathi Shankaralingappa; Michael L Anthony; Tummidi Santosh; Kanakapudi Josephain; Prabhakaran Nagendran; Hima Gopinath (Wolters Kluwer Medknow Publications, 2022)
Tuberculids are considered to be a hypersensitivity reaction to endogenous tuberculosis (TB). Papulonecrotic tuberculid (PNT) is a rare tuberculid occurring in <5% of active TB. An 18-year-old male presented with recurrent necrotic papules for 6 years on limbs, trunk, and neck which healed with scars. Biopsy from lesion revealed caseating granulomas with lymphohistiocytic vasculitis. Ziehl-Neelsen stain was negative for acid-fast bacilli, but Mantoux was strongly positive. The polymerase chain reaction was not done due to monetary constraints. The final diagnosis of PNT was confirmed and he was started on anti-tubercular treatment (ATT) for which he responded. PNT should be treated as a sentinel lesion and a meticulous search for systemic involvement of TB should be carried out. Awareness about PNT is essential for its diagnosis and to institute ATT at appropriate time.